THE FORENSICS EXPERT IN THE COSTA RICAN CRIMINAL PROCESS. THE RESEARCHER´S VISIÓN ON THE CONTRIBUTION OF THE FORENSIC PATHOLOGIST DURING THE INVESTIGATION, WITH SPECIAL RELEVANCE IN THE SITES OF HOMICIDES DUE TO THE SÍNDROME OF THE SYNDROME OF THE ATTACKE - Jiménez Rodríguez, Daniel (2022)
Given the birth of accusatory criminal systems, forensic sciences have assisted the administration of justice in the search for the truth of the facts, and the Costa Rican system has not been the exception. The objective of the text to be developed is to present the vision of the special agent of investigation, regarding the participation of the forensic expert during the investigation stage, with special emphasis during the attention of the death scene in cases where the victim is a child, and he suffered of child abuse Syndrome. The following article aims to illustrate police practice during this type of scenario, and to highlight the validity and relevance of the intervention of the forensic expert, from the beginning of the stage of the criminal process; which helped the various procedural subjects, to the creation of their respective theories of the case.